Co-encapsulação de fármacos antimaláricos: estudo de formulação e avaliação da toxicidade em C. elegans - Pereira, Kélle Velasques (2016)
Malaria is a major problem of public health worldwide and has caused numerous cases of incidence and mortality. Amongst the therapeutic arsenal for the treatment of malaria stands out quinine (QN). However, it has some limitations in its use, for example, the high doses required during treatment and its adverse effects. Curcumin (CR) is a natural compound that has demonstrated various therapeutic activities, among them the antimalarial activity, but its use orally is also compromised by its low solubility in water. Encapsulation in polymeric nanocapsules (NCs) is a pharmacological approach that can overcome the difficulties of the therapeutic use of these two compounds. In addition, the biological evaluation of these new formulations in an in vivo model is relevant. The present study aimed to develop and characterize NCs by nanoprecipitation method and to characterize according to the diameter, polydispersity index, pH, zeta potential, content, encapsulation rate and assess their safety in Caenorhabditis elegans. All nanocapsules prepared had an average diameter of about 200 nm to 274 nm and QN to CR, slightly acidic pH and negative zeta potential. In the pseudo-phase study the NCs showed a behavior type III to type VI and QN of CR. Regarding the assessment of toxicity, the worms exposed the NCs showed a higher survival, while the drug in free form had a mortality. In addition, it was observed that free drugs decreased reproductive capability of worms, while the CN did not cause significantly difference in this parameter compared to control. For the longevity test the worms exposed to the NC showed an increase in the average lifetime compared to control. It was possible to observe by fluorescence microscopy that the NCs were absorbed orally by worms. Co-encapsulation of QN and CR was effective, minimizing the toxic effects caused by chronic exposure of their free forms.